2017
DOI: 10.1002/wcs.1449
|View full text |Cite
|
Sign up to set email alerts
|

New perspectives on the neurophysiology of primate amygdala emerging from the study of naturalistic social behaviors

Abstract: A major challenge of primate neurophysiology, particularly in the domain of social neuroscience, is to adopt more natural behaviors without compromising the ability to relate patterns of neural activity to specific actions or sensory inputs. Traditional approaches have identified neural activity patterns in the amygdala in response to simplified versions of social stimuli such as static images of faces. As a departure from this reduced approach, single images of faces were replaced with arrays of images or vid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 82 publications
(197 reference statements)
1
20
0
Order By: Relevance
“…The amygdala is known to play an important role in the response to facial expressions that convey fear, although its involvement in emotion processing is broader and not specific for negative emotions only . Interestingly, more recent studies in the monkey showed that the amygdala can process complex stimuli, especially during social interactions related to both positive and negative experiences . Several studies also showed, for example, that the central nucleus of the amygdala likely represents the interface between the motor brain regions controlling specific emotional responses and autonomic/endocrine responses …”
Section: Role Of Motor System and Simulation Mechanisms In Emotion Prmentioning
confidence: 99%
See 1 more Smart Citation
“…The amygdala is known to play an important role in the response to facial expressions that convey fear, although its involvement in emotion processing is broader and not specific for negative emotions only . Interestingly, more recent studies in the monkey showed that the amygdala can process complex stimuli, especially during social interactions related to both positive and negative experiences . Several studies also showed, for example, that the central nucleus of the amygdala likely represents the interface between the motor brain regions controlling specific emotional responses and autonomic/endocrine responses …”
Section: Role Of Motor System and Simulation Mechanisms In Emotion Prmentioning
confidence: 99%
“…131 Interestingly, more recent studies in the monkey showed that the amygdala can process complex stimuli, especially during social interactions related to both positive and negative experiences. 132 Several studies also showed, for example, that the central nucleus of the amygdala likely represents the interface between the motor brain regions controlling specific emotional responses and autonomic/endocrine responses. [133][134][135] Vicarious insula activity has been evidenced during both experience and observation of disgust.…”
Section: Role Of Motor System and Simulation Mechanisms In Emotion mentioning
confidence: 99%
“…For example, a viewer may fixate differentially on averted eyes compared to eyes which are directed at the viewer (eye contact). These dynamics may be different during faceto-face interactions with social partners and even when watching videos, where the social stimulus behaves more naturally (Gothard et al, 2018). The effect of OT on blinking should also be quantified, as blinking is an integral component of a gaze-mediated social interactions (Ballesta & Duhamel, 2015; Ballesta, Mosher, Szep, Fischl, & Gothard, 2016; Cummins, 2012).…”
Section: Studies Of Oxytocin In Non-human Primatesmentioning
confidence: 99%
“…For this study, we chose two tasks that exhibit robust effects after amygdala damage, the human intruder paradigm (Kalin et al, 2004;Machado and Bachevalier, 2008;Raper et al, 2013b;Raper et al, 2013a) and a socioemotional attention task (Adolphs et al, 1994;Adolphs et al, 2005;Chudasama et al, 2009;Machado et al, 2009;Machado et al, 2011;Hadj-Bouziane et al, 2012;Gothard et al, 2018). Given that CNO can be reductively metabolized into the psychoactive compound clozapine (Gomez et al, 2017;Raper et al, 2017;Allen et al, 2018), it was important to establish that CNO administration alone would not impact behavior prior to introducing DREADDs into the amygdala.…”
Section: Discussionmentioning
confidence: 99%
“…Socioemotional Attention Task: Damage to the amygdala has been shown to alter attention toward social cues as well as threats in the environment (Aggleton, 2000;Adolphs et al, 2005;Feinstein et al, 2011;Gothard et al, 2018;Payne and Bachevalier, 2019). To measure changes in attention to social and innate aversive stimuli, subjects' eye movements were monitored using a Tobii T60/T120 eye tracker (Tobii Technology, Mountain View, CA).…”
Section: Behavioral Assessmentsmentioning
confidence: 99%